IMPLEMENTATION OF THE 2013 CURRICULUM IN LEARNING ARABIC LANGUAGE AT MTs NEGERI 1 LAMPUNG TIMUR - Ika Supriyanti (STIT Pringsewu, 2024)
The 2013 curriculum is a curriculum that improves and balances soft skills and hard skills which include aspects of competence, attitudes, skills and knowledge. In this context, K13 seeks to further instill values that are reflected in attitudes that can be directly proportional to the skills students acquire through knowledge at school. Learning Arabic is an important lesson that must be present in every school in Indonesia. So it needs to be implemented well so that learning Arabic will be more effective and it is certain that the 2013 Curriculum will have differences and obstacles in its application in teaching Arabic. From this, the researcher wants to know how to implement Arabic language teaching using the 2013 curriculum. The research method that researchers use is a qualitative approach using the case study method. The data collection technique uses observation, interviews and documentation. And the results of this research are that in learning Arabic at MTs Negeri 1 East Lampung, the 2013 Curriculum has been implemented even though it is not yet optimal, for the tarkib al sum material, qiro'ah material and kitabah material, it has been implemented well, in the learning process it has covered six The main steps in learning use a scientific approach, while for the material speaking skills and listening skills or istima' and mufrodat because in this material, students cannot yet create, which in this case, creating is one of the six main steps in learning using 2013 curriculum, however, for the tarkib al quantity material, reading skills or qiro'ah and writing skills or kitabah, can be applied optimally. There are a few obstacles, especially for mufrodat and tarkib al sum materials, due to the lack of supporting books or references such as the Nahwu Shorof book, Arabic dictionaries available in madrasah.